Examining the Effects of Celebrity Endorser’s Credibility, Congruency and Meaning transfer on Purchase Intention of Skincare Products: An Empirical Research in East China - peng, cheng (2015)
Celebrity endorsement strategy is widely used by marketers for the purpose of increasing sales and extending the market shares. Celebrity endorsers have proved with positive impacts on purchase intention by many researchers. However, the current findings about the effects of celebrity endorsement on purchase intention are still equivocal, owing to several different dimensions of celebrity endorsement. For example, source credibility of celebrity, celebrity congruency and meaning transfer of celebrity. Therefore, it is necessary to study these three factors in order to examine its effects on consumer purchase intention.